2018
DOI: 10.1038/s41388-017-0086-y
|View full text |Cite
|
Sign up to set email alerts
|

Pyruvate kinase M2 promotes pancreatic ductal adenocarcinoma invasion and metastasis through phosphorylation and stabilization of PAK2 protein

Abstract: Pyruvate kinase muscle isozymes (PKMs) have crucial roles in regulating metabolic changes during carcinogenesis. A switch from PKM1 to PKM2 isoform was thought to lead to aerobic glycolysis promoting carcinogenesis, and was considered as one of the cancer signatures. However, recent evidence has argued against the existence of PKM isoform switch and related metabolic effects during cancer progression. We compared the effects of PKM1 and PKM2 in cell invasiveness and metastasis of pancreatic ductal adenocarcino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(39 citation statements)
references
References 44 publications
2
37
0
Order By: Relevance
“…Pyruvate kinase muscle isozymes (PKMs) play an important role in adjusting metabolic changes during carcinogenesis. Cheng et al (2018) [59] revealed that the increased expression of PKM1 and PKM2 affected cell invasion and migration in PDAC cells. Lu et al (2018) [60] analyzed the related microarray datasets (GSE15471, GSE62452, GSE102238, GSE62165, and GSE16515) and identified the top 21 genes with high connectivity degrees; among them, PLAU is a plasminogen activator, ITGA3 plays a vital function in EMT, and the high expression of PLAU and ITGA3 is related to poor survival, consistent with the current research.…”
Section: Discussionmentioning
confidence: 99%
“…Pyruvate kinase muscle isozymes (PKMs) play an important role in adjusting metabolic changes during carcinogenesis. Cheng et al (2018) [59] revealed that the increased expression of PKM1 and PKM2 affected cell invasion and migration in PDAC cells. Lu et al (2018) [60] analyzed the related microarray datasets (GSE15471, GSE62452, GSE102238, GSE62165, and GSE16515) and identified the top 21 genes with high connectivity degrees; among them, PLAU is a plasminogen activator, ITGA3 plays a vital function in EMT, and the high expression of PLAU and ITGA3 is related to poor survival, consistent with the current research.…”
Section: Discussionmentioning
confidence: 99%
“… 31 PKM2 has also been reported to phosphorylate STAT3 at Y705, thereby enhancing its transcriptional activity. 16 More recently, PKM2 has been found to phosphorylate H2AX, 32 PAK2, 33 and SNAP-23. 34 While the ability of PKM2 to directly phosphorylate proteins has been challenged, 35 unbiased proteomic screens have identified over 900 substrates for PKM2.…”
Section: Discussionmentioning
confidence: 99%
“…Pyruvate kinase-M2 (PKM2) is a major oncogenic ATPgenerating glycolytic enzyme and is particularly overexpressed in pancreatic cancer. [12][13][14][15][16][17] PKM2 has a low catalytic activity, producing a bottleneck at the terminal end of glycolysis. 12,18 This is advantageous to cancer cells as it results in the buildup of glycolytic intermediates, which are then utilised in nucleotide and lipid biosynthesis to aid rapid proliferation.…”
Section: Introductionmentioning
confidence: 99%